2021
DOI: 10.3390/cells10020258
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Effects of Taurine on Heat-Induced Bovine Mammary Epithelial Cells In Vitro

Abstract: It is a widely known that heat stress induces a reduction in milk production in cows and impairs their overall health. Studies have shown that taurine protects tissues and organs under heat stress. However, there have yet to be studies showing the functions of taurine in mammary alveolar cells-large T antigen (MAC-T) (a bovine mammary epithelial cell line) cells under heat shock. Therefore, different concentrations of taurine (10 mM, 50 mM, and 100 mM) were tested to determine the effects on heat-induced MAC-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Taurine alleviated the rates of apoptosis in bovine mammary epithelial cells and suppressed the expression of heat shock factor 1 (HSF1) mRNA and protein under heat-stress conditions, but not HSP90 [53]. Our findings align with the research conducted by Bai, Li, Yu, Zhou, Kou, Guo, Yang and Yan [53], as we also observed selective response of CopA3 towards HSPs. The compounds under investigation as heat-stress relievers have shown the capability to restore apoptosis and protein expression levels, which were increased by heat stress, back to normal conditions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Taurine alleviated the rates of apoptosis in bovine mammary epithelial cells and suppressed the expression of heat shock factor 1 (HSF1) mRNA and protein under heat-stress conditions, but not HSP90 [53]. Our findings align with the research conducted by Bai, Li, Yu, Zhou, Kou, Guo, Yang and Yan [53], as we also observed selective response of CopA3 towards HSPs. The compounds under investigation as heat-stress relievers have shown the capability to restore apoptosis and protein expression levels, which were increased by heat stress, back to normal conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Taurine, which is recognized as a natural antioxidant found in various animal tissues [51], has also been investigated as a potential remedy for heat stress [52]. Taurine alleviated the rates of apoptosis in bovine mammary epithelial cells and suppressed the expression of heat shock factor 1 (HSF1) mRNA and protein under heat-stress conditions, but not HSP90 [53]. Our findings align with the research conducted by Bai, Li, Yu, Zhou, Kou, Guo, Yang and Yan [53], as we also observed selective response of CopA3 towards HSPs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the apoptosis rate of mammary epithelial cells in dairy cows was increased under HS conditions, and cytoskeletal and cell transport functions were disturbed (11)(12)(13). In modern dairy farms, managers adopt a variety of approaches to alleviate or prevent the occurrence of HS in dairy cows, and some feed additives [betaine (14), choline (15), taurine (16) and methionine (17)] seem to be effective in alleviating negative effects of HS.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that taurine supplementation promotes milk fat and protein synthesis and alleviates oxidative stress and inflammation in bovine mammary epithelial cells ( 20 , 21 ). Moreover, taurine can reverse the decreases in the activity of superoxide dismutase and glutathione peroxidase induced by HS, then alleviate cellular oxidative stress, and thus protect bovine mammary epithelial cells against HS ( 22 ). Furthermore, the protective effect of taurine on mammary glands has been achieved by attenuating mammary gland epithelial integrity damage and inflammatory response under HS conditions ( 23 ).…”
Section: Introductionmentioning
confidence: 99%